Dam invaders: impoundments facilitate biological invasions into freshwaters. Issue 7 (1st September 2008) - Johnson, Pieter TJ; Olden, Julian D; Vander Zanden, M Jake
Abstract : Freshwater ecosystems are at the forefront of the global biodiversity crisis, with more declining and extinct species than in terrestrial or marine environments. Hydrologic alterations and biological invasions represent two of the greatest threats to freshwater biota, yet the importance of linkages between these drivers of environmental change remains uncertain. Here, we quantitatively test the hypothesis that impoundments facilitate the introduction and establishment of aquatic invasive species in lake ecosystems. By combining data on boating activity, water body physicochemistry, and geographical distribution of five nuisance invaders in the Laurentian Great Lakes region, we show that non‐indigenous species are 2.4 to 300 times more likely to occur in impoundments than in natural lakes, and that impoundments frequently support multiple invaders. Furthermore, comparisons of the contemporary and historical landscapes revealed that impoundments enhance the invasion risk of natural lakes by increasing their proximity to invaded water bodies, highlighting the role of human‐altered ecosystems as "stepping‐stone" habitats for the continued spread of freshwater invaders.